The Influence of Fiscal Decentralization on The Public Expenditure In Indonesia - Djoko Suhardjanto; Eni Jufriyah Sulistyorini; Sri Hartoko (Jurnal Siasat Bisnis, 2009)
The purpose of this research is to investigate the influence of fiscal decentralization components on the public expenditure. This research used data of the local budget realization which consisting of balance fund, others revenue, local original revenue, and public expendi-ture that was obtained from financial statement regencies and municipalities in Indonesia. The selection is based on consideration that regencies and municipalities have similar characteris-tic of economic and geographic and also the result of the research would be expected give a description of general condition. The results of this research proved fiscal decentralization through component of balance fund significantly positive influence in increasing original reve-nues while others revenue is not. Regarding with the public expenditure, both of balance fund and local original revenue positively influence on public expenditure, while others revenue is not significantly influence. Keywords:    Fiscal decentralization, Balance Fund, Other Revenues, Local Original Revenue, Public Expenditure.